PERAN BADAN PERMUSYAWARATAN DESA TALAWE KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Haeruddin Syarifuddin; Abdul Jabbar; Muhammad Ikbal (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
This study aims to determine the role of the Village Consultative Body in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency, which has an important position in the village government system. In Article 3 of Permendagri No.110/2016 it is stated that the purpose of setting up the Village Consultative Body is to emphasize the role of the Village Consultative Body in the administration of Village Government, to encourage the Village Consultative Body to be able to accommodate and channel the aspirations of the Village community, to encourage BPD in realizing good governance in the village. . research based on this method is a population survey research is a generalization area consisting of objects or subjects that have certain qualities and characteristics determined by researchers to be studied and then drawn conclusions. Data collection techniques are the most strategic steps in research because the main purpose of this research is to obtain data. The data collection techniques used in this study are as follows: Observation, Interview, Questionnaire, Literature Study. Research using quantitative research methods, the data in this study must be converted into numbers. Descriptive statistics are statistics that describe phenomena or data characteristics. Regarding the role of the Consultative Body in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency. Of the three indicators, including: active role, participatory role, passive role, obtained an average percentage of 39.2% is in the Less Good category.